A Reprise on Herbert v. Lando and the Law of Defamation - HUNTER, Howard (Institutional Knowledge at Singapore Management University, 1982)
Three and a half years ago, in an article, published in a symposium issue of the Kentucky Law Journal focusing on the first amendment, I examined the United States Supreme Court decision of Herbert v. Lando. The Court held that reporters, editors and publishers are not protected by any "editorial privilege" from "state of mind" inquiries during discovery in a defamation case governed by the standard of liability set forth in New York Times Co. v. Sullivan. The Supreme Court decision in Lando stirred a mild flurry of academic comment, partly because it reversed the Second Circuit's broad ruling in favor of an editorial privilege. More interestingly, the case aroused a widespread howl of indignation from the press which passionately suggested that Lando had undermined the foundations of the first amendment. The academic commentators, including me, generally did not consider Lando to be an exceptional case, nor was there much concern that Lando would adversely affect media defendants in defamation suits.